PERLINDUNGAN HUKUM BAGI PEMILIK SERTIPIKAT HAK MILIK YANG DIKLAIM SEBAGAI MILIK MASYARAKAT ADAT DI KABUPATEN DAIRI - MERRY CHRISTINA GULTOM (PREMISE LAW JURNAL, 2013)
ABSTRACT Land has a high value, viewed from any single point of view. It is used as a place for dwelling, making a living, having offspring, and performing traditional and religious rituals. Since there is a close relationship between people and land, this harmonious relationship between people and land needs to be taken care of, based on the same perception. All at once, it is a token of being grateful to God’s blessing so that land grows to be the root of prosperity which is dreamed either by individuals or by community. Land is so valuable that man as social beings will defend their land with all kinds of efforts. In an adat law community, people and land where they dwell in is very closely related, and this relationship is based on religious magic. People’s right on land is called landlordism or communal right of disposal. The nature of adat land in Indonesia is communal which means that it is owned by all members of adat community. In reality, the implementation of communal right of disposal or the other rights of adat law community still exists, but when communal right of disposal comes to an end, it is no longer validated. Adat land can be extinct or abolished when there are no more offspring or no connection with their land anymore, but the conversion of the land rights can be requested to be administered to the local Land Office in order to obtain legal protection for legal certainty on the land ownership. The research was conducted in Dairi District. Keywords: Legal Protection, Certificate, Adat Community